Divergence of thermal physiological traits in terrestrial breeding frogs along a tropical elevational gradient. Issue 9 (6th April 2017) - von May, Rudolf; Catenazzi, Alessandro; Corl, Ammon; Santa‐Cruz, Roy; Carnaval, Ana Carolina; Moritz, Craig
Abstract: Critical thermal limits are thought to be correlated with the elevational distribution of species living in tropical montane regions, but with upper limits being relatively invariant compared to lower limits. To test this hypothesis, we examined the variation of thermal physiological traits in a group of terrestrial breeding frogs (Craugastoridae) distributed along a tropical elevational gradient. We measured the critical thermal maximum (CTmax ; n  = 22 species) and critical thermal minimum (CTmin ; n  = 14 species) of frogs captured between the Amazon floodplain (250 m asl) and the high Andes (3, 800 m asl). After inferring a multilocus species tree, we conducted a phylogenetically informed test of whether body size, body mass, and elevation contributed to the observed variation in CTmax and CTmin along the gradient. We also tested whether CTmax and CTmin exhibit different rates of change given that critical thermal limits (and their plasticity) may have evolved differently in response to different temperature constraints along the gradient. Variation of critical thermal traits was significantly correlated with species' elevational midpoint, their maximum and minimum elevations, as well as the maximum air temperature and the maximum operative temperature as measured across this gradient. Both thermal limits showed substantial variation, but CTmin exhibited relatively faster rates of change than CTmax, as observed in other taxa. Nonetheless, our findings call for caution in assuming inflexibility of upper thermal limits and underscore the value of collecting additional empirical data on species' thermal physiology across elevational gradients. Abstract : A widely held assumption is that climatic niches have not changed along the history of species, both within and among closely related species. Using a phylogenetic framework, this study documents high variability in both elevational distribution and tolerance to heat among closely related species. Our findings suggest that thermal traits in ectotherms can adjust rapidly and so cannot be simply extrapolated from relatives.